Characterization of Micro‐ and Nanoscale LuPO4:Pr3+, Nd3+ with Strong UV‐C Emission to Reduce X‐Ray Doses in Radiation Therapy. (29th August 2019) - Espinoza, Sara; Müller, Matthias; Jenneboer, Heike; Peulen, Lukas; Bradley, Tiara; Purschke, Martin; Haase, Markus; Rahmanzadeh, Ramtin; Jüstel, Thomas
Abstract: UV‐C emitting nanoscale scintillators can be used to sensitize cancer cells selectively against X‐rays during radiation therapy, due to the lethal DNA lesions caused by UV‐C photons. Unfortunately, nanoscale particles (NPs) show decreased UV‐C emission intensity. In this paper, the influence of different Nd 3+ concentrations on the UV‐C emission of micro‐ and nanoscale LuPO4 :Pr 3+ is investigated upon X‐ray irradiation and vacuum UV excitation (160 nm). Co‐doped LuPO4 results in increased UV‐C emission independent of excitation source due to energy transfer from Nd 3+ to Pr 3+ . The highest UV‐C emission intensity is observed for LuPO4 :Pr 3+, Nd 3+ (1%, 2.5%) upon X‐ray irradiation. Finally, LuPO4 NPs co‐doped with different dopant concentrations are synthesized, and the biological efficacy of the combined approach (X‐rays and UV‐C) is assessed using the colony formation assay. Cell culture experiments confirm increased cell death compared to X‐rays alone due to the formation of UV‐specific DNA damages, supporting the feasibility of this approach. Abstract : LuPO4 :Pr 3+, Nd 3+ shows strong UV emission causing DNA damage . Nd 3+ is used as a co‐activator in LuPO4 :Pr 3+ to improve UV emission in the nanoscale range. Different particle sizes and excitation sources are studied. The biological efficacy of the UV emission to inactivate cancer cells is demonstrated using LuPO4 :Pr 3+, Nd 3+ nanocrystals combined with X‐rays, proving its potential as a radiosensitizer.